Implementasi Model Pembelajaran Project Based Learning (PJbL) pada Kemampuan Berpikir Kritis Siswa di SD Negeri 7 Pemenang Barat Tahun Pelajaran 2023/2024 - Nurhadijah, Nurhadijah; Hadi, Rusman; Dwipa, Lalu Belik Made (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2024)
This research uses a type of qualitative research with a case study approach, which aims to examine the Project Based Learning (PjBL) learning model on students' critical thinking abilities. The subjects in this research were class IV students at SD Negeri 7 Juara Barat with a total of 23 students. The data collection techniques used are observation, interviews and documentation techniques. Then the data analysis used in this research is: data condensation, data presentation, and drawing conclusions. The results of this research show that in general in the learning process, teachers carry out several stages, including the planning, implementation and evaluation stages. The planning stage is the stage where the teacher plans and designs the learning process, such as analyzing material, formulating objectives and compiling assessment tools. The implementation stage is the stage where the teacher carries out the learning process in the classroom by creating an active and conducive learning atmosphere. The evaluation stage is the stage where the teacher carries out the process of collecting data, to determine the extent of students' abilities in achieving educational goals. At the implementation stage, the teacher carries out the learning process in the classroom using the Project Based Learning (PjBL) learning model, which consists of six stages, namely the stage of asking basic questions, designing and planning projects, preparing project creation schedules, monitoring students, testing results and evaluating . Based on the stages of the Project Based Learning (PjBL) learning model, it can develop students' critical thinking skills which are characterized by students being able to ask, answer questions, explain, conclude and create projects according to the indicators of critical thinking skills, namely providing simple explanations, building basic skills, concluding. , provide further explanations and determine strategies and techniques.